Use of game fauna by Fulni-ô people in Northeastern Brazil: implications for conservation - Josivan Soares da Silva; André Luiz Borba do Nascimento; Rômulo Romeu Nóbrega Alves; Ulysses Paulino Albuquerque (BMC, 2020)
Abstract Background Due to the influence of several factors on the hunting of game meat, we investigated how the seasonality of the environment, the abundance, and the biomass of wild animals, as well as the proximity to these resources, can affect the hunting. Methods The research was developed with the Fulni-ô people in the municipality of Águas Belas, Agreste of Pernambuco, Northeast of Brazil. In order to do this, we applied snowball sampling to select the participants. Data from potentially useful game species were obtained from lists and semi-structured interviews to register their particular kind of uses, capture periods (daytime, night, or both), preferences, and perceived abundance. The hunters who allowed their game meat captured to be weighed and identified were followed for 1 year. Results Our records pointed to a vast repertoire of potentially hunting animals. However, we did not verify relationships between the abundance, seasonality, and biomass of the animals that were hunted by the Fulni-ô. We observed a total of 209,866 (kg) of game meat hunted in the studied group, belonging to 23 species, distributed in three taxonomic groups, the birds being the most representative group with 59% of total reported. Conclusion Such consumption by the group is well below in terms of biomass when compared to other ethnic or local groups in other regions of Brazil, or in Caatinga areas, characterizing an activity much more of cultural character than subsistence. Also, the use of game meat among the Fulni-ô seems to be actively directed to the preferred species, suggesting that in the case of an urbanized indigenous community, where other sources of income are available, the demand for game meat is lower when compared to other ethnic groups.